Effect of Six Weeks of Progressive Jump-Landing Training on Jump Shooting Accuracy and Knee Valgus Angle in Male Basketball Players with Dynamic Knee Valgus - Saeed Ghobadi Nezha; Seyyed Hosein Hoseini; Ali Asghar Norasteh (Biyumikānīk-i varzishī)
Objective: Dynamic Knee Valgus (DKV) causes many acute and chronic knee injuries during deceleration and landing in sports activities and can affect the athletes’ specific skills. This study aims to investigate the effect of 6 weeks of progressive jump-landing training on jump shooting accuracy and knee valgus angle in male basketball players with DKV. Methods: This is a quasi-experimental study conducted on 24 male basketball players with DKV in Mazandaran, who were selected purposefully. They were randomly divided into training and control groups. Their jump shooting accuracy was assessed by Boddington’s Basketball Jump Shooting Accuracy Test, and their DKV angle was measured by a two-dimensional evaluation method in Quinoa software. In addition to their routine exercises, the training group performed the jump-landing training for 6 weeks at 3 sessions per week, while the control group performed their usual exercises only. In order to compare the two study groups, ANCOVA was used. Results: The progressive jump-landing program had a significant effect on jump shooting accuracy (P=0.001) and DKV angle (P=0.001). Conclusion: Six weeks of progressive jump-landing training can improve the jump shooting accuracy and knee valgus angle in basketball players with DKV. Therefore, jump landing exercises are recommended for improving the jump shooting skill and knee alignment in these athletes.